Academic Burnout in Mexican Medical Students: A Critical Review of Prevalence, Risk Factors, and Gaps in Intervention - Puig-Lagunes, Angel Alberto; Mendez-Lara, Lessa Alessandra; Ortiz-Cruz, Fabiola (International Journal of Medical Students, 2025)
Academic Burnout Syndrome (ABS) is defined as a state of exhaustion and disengagement related to the educational environment that affects university students in diverse disciplines. The combination of an intense academic load, high expectations, competitiveness among students, and other factors during their education has the potential to affect negatively, among other things, academic performance, decision-making ability, physical and mental well-being, self-esteem, and overall quality of life. This review aims to delineate the most prominent findings and advancements on ABS in medical students in Mexico while identifying areas that require further attention and developing research proposals to enhance the comprehension and treatment of this problem. A critical narrative analysis was conducted following an exhaustive bibliographic search for articles in both English and Spanish across a range of databases, including PubMed, Google Scholar, Redalyc, SciELO, and DOAJ. The search took place in the period from January to July 2023. Randomized trial articles and original research were included in the analysis. Meta-analyses and incomplete studies were excluded while the articles were reviewed, resulting in a final selection of 22 relevant articles. Despite the vast number of studies conducted on ABS in medical students in Mexico, a significant part focuses on descriptive characteristics. At the same time, other aspects, such as prevention, treatment, and awareness of this problem, are often overlooked. To effectively address ABS, academic communities must implement comprehensive preventive and curricular measures that prioritize the well-being of students, fostering a healthy and supportive learning environment.